2020
DOI: 10.1016/j.eclinm.2020.100265
|View full text |Cite
|
Sign up to set email alerts
|

A suicide prevention initiative at a jumping site: A mixed-methods evaluation

Abstract: Background: Gap Park in Sydney, Australia has historically been recognised as a suicide jumping site. In 2010À2011 the Gap Park Masterplan initiative implemented a series of suicide prevention measures. This study applied a mixed-methods design to evaluate the effectiveness of the Masterplan in reducing suicides. Methods: Data from the Australian National Coronial Information System (NCIS) was examined to compare suicides at Gap Park before and after the Masterplan was implemented. This was complemented with q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…Any movement in that region beyond the arrival of trains would send an alert to station staff. Similarly, 2 other studies described a similar approach at a cliff located in Sydney, Australia [ 5 , 7 ]. Unlike the metro station, this outdoor site was much larger and with extremely uneven geography, leading to less complete CCTV coverage.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Any movement in that region beyond the arrival of trains would send an alert to station staff. Similarly, 2 other studies described a similar approach at a cliff located in Sydney, Australia [ 5 , 7 ]. Unlike the metro station, this outdoor site was much larger and with extremely uneven geography, leading to less complete CCTV coverage.…”
Section: Resultsmentioning
confidence: 92%
“…Pedestrian Tracking with Group Functionality. Three groups of people are detected in the scene: (1,2), (5,7), and (9,12). Each pedestrian is represented by a unique ID, and groups enclosed by blue rectangles.…”
Section: Behavior Identification Through Computer Visionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Police Open access officers shared their anxiety and sense of responsibility for suicide victims and their families. 57 Impact of perceived legitimacy and public stigma Non-legitimacy mental illness and impact on seeking help Many studies reported how often mental health crises were not considered a 'real' emergency. FRs reported that responding to MHC was 'babysitting', frustrating and a waste of time and resources, reporting that it damaged their public image.…”
Section: Acknowledging Versus Criminalising Mental Illness and Proced...mentioning
confidence: 99%
“…Ross et al report trends in suicide deaths at a hotspot site (Gap Park, Sydney, Australia), where a multilevel means restriction strategy (The Gap Park Self-Harm Minimisation Masterplan) has been implemented [3]. A novel mixed-methods approach was used to evaluate the effectiveness of the Masterplan in the years following its implementation in 2010.…”
mentioning
confidence: 99%